Influence of rough micro-threaded and laser micro-textured implant-neck on peri-implant tissues: A systematic review - Wayel Mohammed Huraib; Fawaz Pullishery; Thamer Abdulmohshin Al-Ghalib; Adham Abdulmajeed Tash Niyazi; Haitham Binhuraib; Mahmoud El Homossany; Malak Saeed Bamigdad (Saudi Dental Journal)
Background and objective: This systematic review aimed to explore clinical outcomes of marginal or crestal bone level (MBL) and soft tissue status around implants, following the placement of rough micro-threaded/laser-microtextured surface (LMS) implants. These outcomes are compared with those following the placement of smooth machined-neck implants. Materials and methods: Using EBSCO Information Services, we conducted a web-based search of databases such as the PubMed, Scopus, and EMBASE, for relevant English-language scientific papers published between January 2013 and August 2022. Prospective or retrospective controlled cohort studies and randomized controlled trials (RCTs) investigating the role of rough micro-threaded/LMS implant necks on MBL, sulcular probing depth (PD), and/or clinical attachment loss, were included in this review. Results: From a comprehensive literature search of 247 articles, 6 RCTs, 5 prospective studies, and 4 retrospective studies (n = 15) fulfilled the eligibility criteria. MBL with rough micro-threaded implant necks ranged from 0.12 ± 0.17 mm to 3.25 ± 0.4 mm after loading. The smooth machined-neck implants without a micro-threaded neck had a loading MBL of 0.38 ± 0.51 mm to 3.75 ± 0.4 mm. Micro-threaded implant necks showed much lower MBL than machined-neck implants. LMS implant necks had a lower peri-implant PD than machined-neck implants after 3 years of early loading (2.3 ± 0.7 mm vs. 3.8 ± 0.8 mm). The experimental and control groups showed similar gingival recessions (1.08 ± 0.4 mm vs. 2.46 ± 0.3 mm). Meta-analysis was not feasible owing to heterogeneity of the studies. Conclusion: Under functional loading, a roughened micro-threaded design for the implant neck could significantly lower MBL. Furthermore, PD and MBL were much lower around LMS neck implants than those around machined-neck or micro-threaded implants.